Jamaica : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper analyzes Jamaica's experience of low growth despite consistently high investment rates. It suggests that the link between public debt and productivity is part of the answer to the puzzle. The paper considers Jamaica's debt management strategy and its optimal debt structure. It also reviews the institutional framework for debt management in Jamaica, and presents a newly constructed dataset that documents Jamaica's notable market access to long-maturity, fixed interest rate, and domestic currency bond placements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet